Becoming women: period. Perceptions of barriers and facilitators to menstrual hygiene management programs for Pakistani girls - Proff, Alexandria Alisa; Fatima, Surhan; Limón, Mónica Lorena Sánchez (Frontiers in Public Health, 2023)
Discussions on and around menstruation are often considered a cultural taboo in many parts of Pakistan. Mostly, individuals avoid discussing menstruation and lack awareness about its related health and hygiene issues. Sexual health education is entangled in a complex myriad of social and cultural stigmas. Limited knowledge and lack of access to Menstrual Health Management (MHM) resources decrease the self-confidence of girl students and lead to reluctance to seek help or advice. This quantitative study aimed to gain a deeper understanding of the intersectionality of the influences leading to barriers and facilitators of access to the MHM Program in a public school in the Hyderabad district and utilize this information to construct a framework for evaluation of the WASH in Schools Program. This study sampled all girls’ elementary and higher secondary schools in the Hyderabad District. Due to limitations of time and access during the global Covid-19 pandemic, the researchers collected data from more than 100 school leaders and teachers regarding the MHM facilities in their schools through an online self-administered survey. The data were then analyzed in SPSS for frequencies, mean scores, and standard deviation. The results suggest that school leaders and teachers of the Hyderabad district perceive MHM facilities to be significantly low in terms of both resources and policies. Schools worldwide are introducing life skills, hygiene, good health, and wellness subjects. Pakistan needs to change its educational policy for the welfare of females, who comprise a magnanimous 48.54% of its population. Moreover, with the planning and implementation of programs such as WASH in Schools (WinS), the perceptions of barriers and facilitators to MHM facilities in Pakistan must be studied to fight the taboo and raise awareness about the same.